Manajemen Bimbingan Konseling dalam Menangani Kenakalan Siswa di Madrasah Tsanawiyah Mafatihul Huda Cirebon - Asep Kurniawan (Oasis : Jurnal Ilmiah Kajian Islam, 2019)
Problematic and naughty students can almost be found in every school, especially the development of children who tend to want to try something new.  This is a trigger factor for student delinquency.Handling students’ delinquency is the task of the guidance and counseling teacher.Therefore, madrasa must have its management to deal with students’ problems. The purpose of the study was to reveal in depth the management of guidance and counseling in dealing with MTs Mafatihul Huda students’ delinquency.This is a case studies-qualitative research.The results of the study revealed that student delinquency were ditching, smoking, riding truck. The causes were family, environment and peers. This situation was responded to by MTs Mafatihul Huda through management of counseling and guidance. The stages were planning, organizing, implementing and evaluating. This is not in accordance with its implementation, however, because it was not strict in handling students’ delinquency. In addition, guidance and counseling teachers did not intensively overcome students’ delinquency.